TINJAUAN SISTEMATIS TERHADAP PERSYARATAN MANAJEMEN PERUBAHAN DALAM PROYEK PENGEMBANGAN PERANGKAT LUNAK - Safitri, Anita (Universitas Negeri Surabaya, 2022)
Changes in software development are unavoidable and can occur due to changing needs of users, stakeholders, and the presence of new technologies. Analysis of the impact of changes greatly affects the cost and time of project work that can affect the success of the project. With the analysis, can help reduce the impact caused. Therefore, proper change management in software development projects is required. In this paper we present a review of the need for change management in software development. The writing of this paper is done to answer the problems that arise based on the discussion of the journals studied. The problems include: 1. what are the causes of change management, 2. What is the impact of change? 3. What methods can be used to cope with change? 4. What tools can be used to cope with change? The method used in writing this review is to draw conclusions based on the discussion obtained from the grouping of journals related to change management and the need for change management sourced from ScienceDirect and IEEE. The results obtained from this review are to answer four questions that arise and draw conclusions about the methods and tools that are often used in large case studies in change management. The method that is often used to support the management of requirements change is Requirements Change Management (RCM). RCM consists of 3 stages (1) Understanding changes (2) Analysis of changes and (3) Finalizing changes to this method can be assisted with web tools. The web is often used to support change management needs because it can be used to manage quantitative and qualitative data. Keywords: Change Management; Software Development, Requirement Change Management (RCM)